The Impact of Lecturer Code-Switching felt by The Students in Online and Offline English Learning at IAIN Bone - Samsinar; Sukardi Weda; Muhammad Tahir (International Journal of Language, Education, and Literature, 2025)
This study was conducted to explore the impacts of code-switching implemented by lecturers in offline and online English classes based on students’ opinions. The research employed a descriptive qualitative approach, with participants consisting of fourth-semester students from the English Department at the State Institute of Islamic Studies of Bone. Participants were chosen using purposive sampling from a class that experienced blended learning and regular use of code-switching during instruction. Data were gathered through semi-structured interviews and documentation. The results showed that students experienced both positive and negative impacts from the use of code-switching in the classroom. Positively, students reported that code-switching helped them improve their vocabulary, understand English more effectively, and better comprehend the subject matter. Many students felt that when lecturers explained English terms using Indonesian, it allowed them to grasp complex ideas more clearly and retain new information more easily. Code-switching was also seen as a tool to reduce confusion and anxiety, especially for students who lacked confidence in their English skills. It enabled a smoother transition into English comprehension and made classroom learning more inclusive. In both online and offline settings, students expressed appreciation for this approach as it allowed them to focus more on the material rather than struggling with unfamiliar language. However, they still get a negative impacts which is from the online classes. The main negative impact stemmed from poor internet connections, which led to unclear audio and pronunciation issues, especially during English portions of the lecture. This made it harder for students to fully understand the content. Despite this, students developed strategies such as note-taking and asking for clarification to overcome these obstacles. Overall, the study concludes that code-switching, when used effectively, serves as a valuable instructional strategy in bilingual classrooms, enhancing comprehension, supporting language development, and helping students participate more confidently in both online and offline learning environments.